Consumer perception of CSR in Portugal: the aftermath of the financial crisis - Barreto, Joana Duarte Silva (2014)
Corporate social responsibility (CSR) literature has largely neglected consumers’ perceptions in the debate regarding the role of CSR in the aftermath of the financial crisis. In that context, this study aims to test the possibility that consumers’ perceptions of CSR level, firm reputation and brand trust, might depend on the type of industry sector of a firm, the level of fit of an initiative or both. By conducting a survey on Portuguese consumers and running a two-way analysis of variance, it suggests that solely the type of industry sector has an effect on consumer perception and that consumers are less tolerable of controversial industries.